Draft Annual Plan 2004-2005 Volume II Government of Assam - Planning Commission (Planning Commission)
Draft Annual Plan 2004-2005, Proposed Outlay (GN - Statement), Draft Annual Plan 2003-04 Proposed Outlay Draft Tenth Plan 2002007 and Annual Plan 20020030 Proposed Outlay Physical Tara at and Achievement Summary Statement Draft Annual Plan (2004 - 2005) Proposals For Programmes/ Projects Statement Regarding Externally Aided Project
Government of Assam